2019
DOI: 10.1016/j.jneuroim.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-beta treated-multiple sclerosis patients exhibit a decreased ratio between immature/transitional B cell subset and plasmablasts

Abstract: Our aim was to quantify circulating B cell subsets; immature/transitional, naïve, CD27 − and CD27 + memory cells and plasmablasts, in relapsing-remitting multiple sclerosis patients treated with IFN-β. The most relevant findings were a significant increase of plasmablasts and a decrease of immature/transitional B cells, resulting in a decreased ratio between those cells in relapse RRMS, together with an increase of CD27 − and CD27 + IgM + memory B cell subsets in both phases of the disease. These alterations p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In IFN-β-treated MS patients, the percentages of naïve and transitional B cells were significantly higher in RRMS than in PMS. These findings are also comparable with previous reports describing an increase in naïve and transitional B cells and a decrease in memory B cells by IFN-β treatment in MS consisting of exclusively or mostly RRMS patients [1214, 22]. It was also reported that the percentage of naïve T cells tended to decrease and that of memory T cells tended to increase in SPMS compared with RRMS [23].…”
Section: Discussionsupporting
confidence: 91%
“…In IFN-β-treated MS patients, the percentages of naïve and transitional B cells were significantly higher in RRMS than in PMS. These findings are also comparable with previous reports describing an increase in naïve and transitional B cells and a decrease in memory B cells by IFN-β treatment in MS consisting of exclusively or mostly RRMS patients [1214, 22]. It was also reported that the percentage of naïve T cells tended to decrease and that of memory T cells tended to increase in SPMS compared with RRMS [23].…”
Section: Discussionsupporting
confidence: 91%
“…The ratio between immature/transitional B cells and plasmablasts can thus be considered as a potential biomarker between phases of RRMS patients. The remission RRMS patients and the healthy subjects presented a similar ratio, and the relapse RRMS patients present a decreased ratio [66]. According to the new and recent data about the recirculation of B cells in RRMS, it seems that the increase of plasmablasts in circulation of relapsing episodes may be due to a migration of these cells from cervical lymph nodes and/or from B cell aggregates described in the meninges of MS patients to the blood marrow in an attempt to promote the immune response [67].…”
Section: B Lymphocytesmentioning
confidence: 84%
“…In our group publications, one can be find the flow strategy with the description of the antibodies used and the mRNA gene expression studies performed in APCs [25], in T cell subsets [41], in γδ T cells [56] and in B cell subsets [66].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations